Climate impact assessment of retail payment services - Niklas Arvidsson; Fumi Harahap; Frauke Urban; Anissa Nurdiawati (Sveriges Riksbank, 2024)
Money and payments are central to modern economies and societies, yet there are increasing concerns over the environmental impacts of various payment services, particularly from a climate perspective. This report examines the climate impact of retail payments in Sweden in 2021, including cash, card, Giro payments, Swish payments, and payment apps. Its goal is to develop a method for measuring the climate impact of existing retail payment services in the Swedish market and to evaluate their individual and aggregate climate impact. The study identifies areas that can be targeted to reduce the overall impact and provide valuable information for sustainable decision-making related to payment services.
Keywords: G29; L89; O39; 330; Environmental Impact; Retail Payment; LCA